PHYTOCHEMICAL SCREENING OF ETHANOLIC EXTRACT OF WHOLE PLANT OF SIDA GLUTINOSA - GUDURU RAJESWARI; LATHA D, SWARNA; SEKHAR KB, CHANDRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the present study is to screen for the phytochemical constituents which are of pharmacological importance present in the ethanolic extract of whole plant of Sida glutinosa (SG). Methods: The ethanolic extract of the dried whole plant of SG is subjected to preliminary phytochemical screening which showed the presence of major phytoconstituents such as phenols, flavonoids, and alkaloids. The extract was screened for its antioxidant activity by 2,2-diphenyl-1- picrylhydrazyl, hydroxyl radical, Iron (III) to Iron (II) reducing activity, and nitric oxide scavenging assay. Further, the ethanolic extract was subjected to fingerprinting technique high-pressure thin-layer chromatography (HPTLC). Reverse phase high-pressure liquid chromatography (Rp-HPLC) was performed to estimate the amount of total phenolics, flavonoids, and alkaloids quantitatively in isocratic mode. Results: Phytochemical screening of the ethanolic extract of the plant showed the presence of pharmacologically important constituents such as alkaloids, flavonoids, phenolics, and terpenoids. The study also revealed the potential antioxidant activity of the extract with IC50 value. The extract fingerprinting through HPTLC revealed the presence of various phytoconstituents. Rp-HPLC showed 0.35±0.12 μg/ml of total phenolics, 0.0013±0.05μg/ml of alkaloids, and 0.00081±0.08 μg/ml of flavonoids. Conclusion: Scientific evaluation of SG which has therapeutic significance was carried out which is an important concept for the standardization of the plant-based drug. Further, there is a need for isolation and characterization of the lead molecules their systemic evaluation for its pharmacological activities.